Ruptured intercostal artery pseudoaneurysm in a patient with blunt thoracic trauma: diagnosis and management. (25th June 2014) - Gutierrez Romero, Diego Felipe; Barrufet, Marta; Lopez-Rueda, Antonio; Burrel, Marta
Abstract : Intercostal artery pseudoaneurysm is an extremely unusual condition, with less than 10 reported cases to our knowledge. Most of them have been associated with surgical interventions or blunt thoracic trauma. The bleeding risk in this kind of lesions is considerable, the majority of them presenting as haemothorax. We present a case of an intercostal artery pseudoaneurysm detected after a blunt thoracic trauma in a patient with signs of acute bleeding. The identification of a small artery pseudoaneurysm as the cause of haemothorax requires knowledge of this possible aetiology as well as detailed attention to the CT technique. Embolisation is considered to be the first therapeutic method in the management of a ruptured pseudoaneurysm. To reduce the risk of failure, the anatomic features and adjacent vessels providing collateral branches must be studied and embolised if needed, with important attention to collateral blood supply arising from the musculophrenic and anterior intercostal arteries.